ANALISIS FRAGMENTASI BATUAN DI QUARRY B PT INDOCEMENT TUNGGAL PRAKARSA, UNIT PALIMANAN, CIREBON - Kurniawati, Savani; Saptono, Singgih; Wiyono, Bagus; Lusantono, Oktarian Wisnu (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
PT Indocement Tunggal Prakarsa carries out limestone distribution activities by drilling and blasting methods. One of the parameters for the success of a blasting activity is rock fragmentation. The distribution of rock fragmentation must meet the company's targets so that production activities run optimally. The purpose of this study is to obtain the ideal blasting geometry in order to produce the fragmentation of the blasted rock in accordance with the company's target, namely the daily uncovered rock volume of 3.000 m3 and the boulder size ≥ 80 cm with a percentage of ≤ 10%. The results of research in the field show that the actual blasting operation of the company's limestone was found to be a problem in the form of fragmentation that did not meet the required criteria. Based on the results of the analysis using Software Split Desktop, there are still many rock fragments resulting from the blasting in the form of boulders ≥ 80 cm with an average percentage of 25,44%. To increase rock fragmentation, a proposed blasting geometry design was carried out using the R. L. Ash, C. J. Konya, and ICI Explosive methods which are expected to reduce the formation of boulders. The proposed blasting geometry design is the ICI Explosive method with a burden of 2,5 m, a spacing of 3 m, and a level height of 6 m which can produce a volume of exposed rock of 3.015 m3 with a powder factor of 0,48 kg/m3 and fragmentation that passes the sieve of 97,77%.